Intra-articular mesenchymal stem cell therapy on a joint capsule rupture in a horse – Case report (Research, Society and Development, 2021)
Joint capsule rupture is an uncommon pathology that leads to intense pain, lameness and is related to the athletic performance impossibility of the animal. This pathology presents controversial therapeutic protocols in the equine clinic and surgery. Therefore, this study aimed to report the use of mesenchymal stem cells associated with arthroscopy and rehabilitation to improve the treatment of joint capsule rupture in equine. A three-year-old, male, Quarter Horse, presenting grade 5 lameness, with four months of evolution, was diagnosed with tibiotarsal joint capsule rupture. The patient underwent arthroscopic surgery, received an intra articular application of mesenchymal stem cells, and a rehabilitation protocol was performed. One year after the treatment and rehabilitation, the horse reestablished its athletic performance, thus indicating the success of the therapy using mesenchymal stem cells associated with surgical treatment and rehabilitation.